2019
DOI: 10.1111/mmi.14232
|View full text |Cite
|
Sign up to set email alerts
|

Three Hfq‐dependent small RNAs regulate flagellar motility in the fire blight pathogen Erwinia amylovora

Abstract: Erwinia amylovora, the causative agent of fire blight disease of apple and pear trees, causes disease on flowers by invading natural openings at the base of the floral cup. To reach these openings, the bacteria use flagellar motility to swim from stigma tips to the hypanthium and through nectar. We have previously shown that the Hfq-dependent sRNAs ArcZ, OmrAB and RmaA regulate swimming motility in E. amylovora. Here, we tested these three sRNAs to determine at what regulatory level they exert their effects an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 58 publications
1
18
0
Order By: Relevance
“…Because deletion of arcZ reduced flhDC mRNA abundance in E. amylovora Ea1189 (31), we hypothesized that loss of lrp acts as a suppressor mutation of Δ arcZ by restoring flhDC transcript levels. To test this hypothesis, we conducted quantitative real-time PCR analyses to quantify transcript levels in the Δ lrp mutants.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Because deletion of arcZ reduced flhDC mRNA abundance in E. amylovora Ea1189 (31), we hypothesized that loss of lrp acts as a suppressor mutation of Δ arcZ by restoring flhDC transcript levels. To test this hypothesis, we conducted quantitative real-time PCR analyses to quantify transcript levels in the Δ lrp mutants.…”
Section: Resultsmentioning
confidence: 99%
“…amylovora, as ArcZ acts as a negative regulator of flagellar motility in other Enterobacteriaceae (32) but is an activator of flagellar motility by transcriptionally activating flhDC in E. amylovora (31). Although we have demonstrated that ArcZ posttranscriptionally regulates lrp in E.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that motility is related with flagella, a potential target of regulation mediated by sRNAs is the dual system composed by the proteins FlhD and FlhC regulating the expression of the rest of the genes in the flagellar regulon (Liu and Matsumura, 1994;Frye et al, 2006). Schachterle et al (2019) researched the involvement of ArcZ, OmrAB, and RmaA in flagellar regulation. First, they found reduced expression levels for regulatory and flagellar structural genes in lack-of-function mutants ( arcZ, hfq, omrAB, and rmaA) in comparison with the WT.…”
Section: Infectious Diseases In Plantsmentioning
confidence: 99%